Improving Planning and Financial Management Literacy for Housewives - Aziza, Elisa Nur; Insani, Hanifah; Amelia, Dhea Arifah; Ammani, Ferry Miftah; Astungkara, Agni (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research aims to enhance financial literacy among families in Duwet Village, Indonesia, focusing on effective financial planning and management. The issue investigated is the low awareness and practice of financial management, which is crucial for maintaining economic stability.Method: The study employed a community service approach, involving socialization sessions targeted at mothers in the Family Welfare Empowerment (PKK) group. Data were collected through participant engagement and feedback, enabling a comprehensive understanding of their financial literacy needs.Practical Applications: The findings have significant implications for improving family financial management practices, promoting economic stability, and enhancing the overall quality of life for families in the community. Increased literacy can lead to better budgeting, savings, and investment decisions.Conclusion: The study demonstrated a notable increase in financial literacy among the mothers of PKK in Duwet Village, emphasizing the importance of community-based education in empowering families for effective financial management.